Europa, una grandeza histórica y moral: el mensaje de Joseph Ratzinger - Rodríguez, María Luisa (UNISCI Discussion Papers, 2007)
The article gathers Ratzinger's thought on Europe and shows how there is a continuity in his line being already Pope. With numerous appointments of different speeches, conversations and other writings, there is described which is the substratum of the European identity, which are its authentic roots. Besides, it calls the attention on the fact that it is not possible to have the fruits that Europe has given throughout these centuries (freedom, human rights, etc) if nor the Europeans themselves do not look after them or they try to forget them or even to hate them.